Penegakan Hukum terhadap Peraturan Daerah Nomor 6 Tahun 2012 Tentang Pengelolaan Sampah dan Sanksi Hukum Serta Kendalanya Di Kota Semarang - Wulansari, Mutia; Listyarini, Dyah; Rochmani, Rochmani (Wajah Hukum, 2024)
Waste, as a byproduct of human activities or natural processes, poses a serious issue due to its substantial and challenging quantity. Problems include waste piles in urban areas and a lack of waste disposal areas around street vendors. This research, titled "Law Enforcement on Regional Regulation No. 6 of 2012 Regarding Waste Management and Legal Sanctions and Challenges in Semarang City," aims to elucidate how the law is applied concerning waste management in Semarang City. This non-doctrinal study employs a normative-empirical juridical approach with a qualitative method. The research is conducted at the Environmental Agency of Semarang City, with primary data sources consisting of interviews with stakeholders from the Waste Management Department and secondary data from legal materials. Data analysis utilizes a qualitative narrative method. Research findings indicate that law enforcement related to Regional Regulation No. 6 of 2012 in Semarang City has been implemented by the local government in accordance with existing provisions. However, deficiencies in community participation persist, such as the habit of improper waste disposal and inadequate waste bin provision. This is attributed to the cultural norm of indiscriminate waste disposal that has become prevalent in society. Additionally, public understanding of "Regional Regulation No. 6 of 2012" regarding Waste Management remains insufficient, particularly regarding the legal penalties for violating the provisions of the regulation.